Pengembangan Produk Masker Wajah Ramah Lingkungan dari Limbah Serbuk Kopi dan Madu Di Desa Rantau Kumpai - Riyan maulana; Andira anggari; Wisnu Ady Saputra; Handes Triwi Bowo; Ferry Desromi (Universitas Merdeka Surabaya, 2025)
The development of an environmentally friendly facial mask product from coffee grounds and honey in Rantau Kumpai Village aims to sustainably utilize local resources and provide added value to the community. This project involves three main stages: planning, implementation, and evaluation. In the planning stage, raw materials were identified, and market needs were analyzed, with coffee grounds and honey selected as the main ingredients in a 2:1 ratio. The implementation stage involved processing the materials, training members of the women's group, and creating a prototype mask. A 4-week product trial demonstrated the mask's effectiveness in improving skin moisture and reducing blackheads. Evaluation results indicated a positive environmental impact through the reduction of coffee waste. This project not only creates a beneficial product but also empowers the community and supports environmental preservation.